Institutions as the Main Determinant in Economic Growth - Hari Nugroho; N. Haidy Ahmad Pasay; Arie Damayanti; Maddaremmeng Andi Panennungi (ETIKONOMI, 2019)
The studies on human capital and technological progress have given incredible insights on how countries in the world differ from one another. Yet there are more than those two reasons to account for differences among countries. There is a third reason why a country would differ in terms of its economic development progress, namely institutional factors. Hence developing institutional indices would give a deeper explanation than a mere theory. On the other hand, we can corroborate the institutional index with the general theory that low-quality institutions will impact an economy negatively. This study seeks to broaden the understanding of causes of economic growth by incorporating institutional index into a semi-endogenous growth model and finds a relationship between that index with human capital and technological progress.JEL Classification: E01, E02, O43